Peran Pendidikan Multikultural dalam Mengelola Keberagaman di Lembaga Pendidikan - Sudirman P; Fajar Farham Hikam; M. Alfiansyah; Mardia Mardia; Hildawati Hildawati (Al-Qalam: Jurnal Kajian Islam dan Pendidikan, 2026)
Indonesia is a country with a high level of diversity, reflected in differences in ethnicity, religion, culture, language, and socioeconomic background. This diversity is also present in educational institutions and needs to be properly managed to prevent conflict, discrimination, intolerance, and social inequality. This study aims to analyze the role of multicultural education in managing diversity, identify its forms of implementation, and examine the challenges faced in its application within educational institutions. This research employs a qualitative approach using the library research method. Data were obtained from scientific articles, books, proceedings, and policy documents published from 2020 to 2026 through Google Scholar, Scopus, and Garuda databases. The data were analyzed using content analysis through the stages of data reduction, categorization, interpretation, synthesis, and conclusion drawing. The findings show that multicultural education plays a strategic role in building an inclusive school culture by integrating the values of tolerance, justice, equality, respect for diversity, and intercultural dialogue into the curriculum, learning process, school culture, and educators’ role modeling. The effectiveness of its implementation is influenced by school policies, teacher competence, inclusive leadership, and collaboration with families and communities. The main challenges include low multicultural literacy among educators, limited training, and insufficient support from the educational environment. The novelty of this study lies in the development of a synthesis framework that integrates curriculum, school culture, leadership, and stakeholder collaboration as a holistic strategy for managing diversity. The results of this study are expected to support the development of more inclusive, democratic, equitable, and relevant educational policies and practices for Indonesia’s pluralistic society.